The clinical psychologist and the management of inpatient pain: a small case series - Childs SR (Dove Medical Press, 2014)
Susan R Childs,1,* Emma M Casely,2,* Bianca M Kuehler,1 Stephen Ward,1 Charlotte L Halmshaw,1 Sarah E Thomas,1 Ian D Goodall,1 Carsten Bantel1,3 1Pain Medicine, Chelsea and Westminster Hospital NHS Foundation Trust, London, 2Anaesthetic Department, Hillingdon Hospital, Uxbridge, 3Section of Anaesthetics, Department of Surgery and Cancer, Faculty of Medicine, Imperial College London, Chelsea and Westminster Hospital Campus, London, UK *These authors contributed equally to this manuscript Abstract: Recent research has confirmed that between 25% and 33% of all hospitalized patients experience unacceptable levels of pain. Studies further indicate that this reduces patient satisfaction levels, lengthens hospital stays, and increases cost. Hospitals are aiming to discharge patients earlier, and this can interfere with adequate pain management. Therefore, the pain service at Chelsea and Westminster Hospital has adapted to this changing model of care. An increasing body of evidence demonstrates that psychological factors are key components of patients’ pain experiences in both acute and chronic pain. Therefore, it is reasonable to suggest a clinical psychologist should be involved in inpatient pain management. This small study discusses three cases that highlight how patient care could be improved by including a clinical psychologist as part of the inpatient pain team. Two cases particularly highlight the active role of the psychologist in the diagnosis and management of common conditions such as fear and anxiety, along with other psychiatric comorbidities. The management therefore employed an eclectic approach adapted from chronic pain and comprising of behavioral, cognitive behavioral, and dialectical behavioral therapeutic techniques blended with brief counseling. The third case exemplifies the importance of nurse-patient interactions and the quality of nurse-patient relationships on patient outcomes. Here, the psychologist helped to optimize communication and to resolve a difficult and potentially risk-laden situation. This small case series discusses the benefits derived from the involvement of a clinical psychologist in the management of inpatient pain, and therefore illustrates the need for novel initiatives for inpatient pain services. However, future research is warranted to validate this approach. Keywords: acute pain, aggression, anxiety, borderline personality disorder, psychology